Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/antiox9121264
|View full text |Cite
|
Sign up to set email alerts
|

β-Naphthoflavone Activation of the Ah Receptor Alleviates Irradiation-Induced Intestinal Injury in Mice

Abstract: Radiotherapy induced gastrointestinal syndrome results from the acute damage of intestinal stem cells, impaired crypts reconstruction, and subsequent breakdown of the mucosal barrier. The toxicity of ionizing radiation is associated with oxidative stress in the intestinal epithelial cells (IECs). Moreover, the rapid proliferation of IECs is a risk factor for radiation damage. β-naphthoflavone (BNF) is an agonist of the aryl hydrocarbon receptor (AhR) and possesses potential antioxidative activity. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…A recent study showed intraperitoneal administration of I3C reduced intestinal inflammation in a mouse model of TNBS-induced colitis via alterations in the gut microbiota [15]. Similarly, other dietary AhR ligands such as tryptophan and β-napthoflavone (BNF) have been shown to attenuate intestinal inflammation [16,17]. However, an in-depth analysis of how I3C through dietary consumption impacts ulcerative colitis as well as ileitis resembling CD has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed intraperitoneal administration of I3C reduced intestinal inflammation in a mouse model of TNBS-induced colitis via alterations in the gut microbiota [15]. Similarly, other dietary AhR ligands such as tryptophan and β-napthoflavone (BNF) have been shown to attenuate intestinal inflammation [16,17]. However, an in-depth analysis of how I3C through dietary consumption impacts ulcerative colitis as well as ileitis resembling CD has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also observed that PMF administration had impacts on gut microbiota in obesity and metabolic syndrome models [ 14 ]. Flavonoids, for example, β-naphthoflavone [ 15 ], were validated to protect cells from radiation-induced injury, yet the protective effects of PMFs on radiation-induced injury in vivo have not been fully discussed.…”
Section: Introductionmentioning
confidence: 99%
“…RIII prevention and treatment research is mainly focused on natural antioxidants (such as vitamins and amino acids), known body protectors, newly synthesized compounds, and biotechnological methods. [7][8][9] A large number of studies have shown that Chinese medicines or extracts may alleviate radiation damage, [10][11][12][13][14] and also have protective effects on radiation enteritis, 15,16 including menthol and ginseng, which are attracting increasing attention due to their low toxicity and are used for radiation protection and treatment. 17,18 Therefore, Chinese medicine compounds may be effective in RIII protection and therapy.…”
Section: Introductionmentioning
confidence: 99%